The effect of COVID-19 pandemic on stock market performance, Malaysia - Pavitra, Ravi (2021)
This study examined the effect of Covid-19 pandemic on stock market performance. It was investigated with the selective sectors which classified under Bursa Malaysia as Consumer, Healthcare, Transportation, Property, and Telecommunication. These five sectors were mainly driven as there are several evidences that discussed on the impact either negatively or positively during the Covid-19 outbreak. All the stocks listed in Bursa Malaysia under this sector was examined to study their performance before and during Covid-19 outbreak. The study period was from 1st January 2020 to 30th June 2020. The subperiods are used as controlled to examine the impact of movement control enforcement, size of firm and sectorial indices on the performance of stock price. The result shows that healthcare and transportation related stocks are not significantly affected by the enforcement of Movement Control Order because the p-value is higher than 0.05 while the property, consumer and telecommunication sectors related stocks shows significant relationship. Moreover, the big cap companies are more significantly affected with the outbreak of pandemic specially property sectors compare to small cap companies. The sectorial index shows that, Healthcare and property are significantly affected during pandemic compare to Consumer Product, Telecommunication & Media and Transportation & Logistic which are not significantly affected by the pandemic of Covid-19.